2014
DOI: 10.1093/aob/mcu026
|View full text |Cite
|
Sign up to set email alerts
|

The effects of localized heating and disbudding on cambial reactivation and formation of earlywood vessels in seedlings of the deciduous ring-porous hardwood, Quercus serrata

Abstract: The results suggested that, in seedlings of the deciduous ring-porous hardwood Quercus serrata, elevated temperature was a direct trigger for cambial reactivation and differentiation of first vessel elements. Bud growth was not essential for cambial reactivation and differentiation of first vessel elements, but might be important for the continuous formation of wide vessel elements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 31 publications
3
33
0
Order By: Relevance
“…Cell divisions in the cambial zone started 5–6 wk earlier than the enlargement of the first EV, attaining longer periods between cambial resumption and the onset of vessel differentiation than previous studies for other ring‐porous species (Frankenstein et al ., ; Kudo et al ., ). Budburst was coupled to the beginning of wall thickening in both species, although secondary wall deposition had not been initiated at the moment of budburst for some first formed Qrob vessels.…”
Section: Discussionmentioning
confidence: 97%
“…Cell divisions in the cambial zone started 5–6 wk earlier than the enlargement of the first EV, attaining longer periods between cambial resumption and the onset of vessel differentiation than previous studies for other ring‐porous species (Frankenstein et al ., ; Kudo et al ., ). Budburst was coupled to the beginning of wall thickening in both species, although secondary wall deposition had not been initiated at the moment of budburst for some first formed Qrob vessels.…”
Section: Discussionmentioning
confidence: 97%
“…This could result from divergent cell responses according to the spatial patterns of auxin concentration (Schrader et al 2003). In this regard, Rathgeber, Rossi & Bontemps (2011) reported that xylem differentiation started earlier in dominant Abies alba trees, while Kudo et al (2014) found that disbudding Quercus serrata seedlings reduced the number and size of earlywood vessels, whose formation was also delayed in a few days.…”
Section: A S C U L a R C A M B I U M A N D G R O W T H C A P A C I T Ymentioning
confidence: 99%
“…Several physiological explanations of vessel-temperature interactions have been discussed in other publications (e.g., Aloni 2015;González-González et al 2014;Pritzkow et al 2016). An influence of stem temperature reaching a threshold of 5°C with a delay of 1-2 weeks before cambial activity begins has been reported by Güney et al (2016) in Lebanon cedar and Kudo et al (2014) found that cambial reactivation in the ring-porous hardwood Quercus serrata is triggered mainly by temperature. The detected close relationship of air heat sum seems to initialize cambial activity and earlywood vessel development directly in a positive manner.…”
Section: Temporal Changes Of Vessel Responsementioning
confidence: 80%